FAKTOR-FAKTOR YANG MEMPENGARUHI PENINGKATAN NILAI TAMBAH SEKTOR PERTANIAN (Studi Kasus Industri Tempe Keripik Kecamatan Jujuhan Ilir, Kecamatan Tanah Tumbuh) - Lupitasari, Mira; Ansofino, Ansofino; Rahmania, Meri (Jurnal Ekonomi dan Pendidikan, 2022)
This study aims to analyze 1) the effect of partial capital on added value, 2) the effect of raw materials partially on added value, 3) the effect of labor partially on added value, 4) the effect of technology partially on added value, 5) the effect of materials. Partial fuel to added value, (6) the effect of capital, raw materials, labor, technology, fuel on the increase in added value in the agricultural sector (a case study of the tempe chips industry in jujuhan ilir sub-district, growing land sub-district). This type of research is descriptive and associative research. The population in this research is the tempe chips industry players in Jujuhan Ilir sub-district, land growing sub-district totaling 38 samples. The results showed that: The results showed that there was a significant influence between the level of capital, raw materials, labor, technology and fuel simultaneously on added value with Fcount 5.05> Ftable 2.51.